The impact of personality traits on residents' attitude towards COVID-19 vaccine: findings from a Chinese cross-sectional study - Xianan Liu; Piriya Somasundram; Xiujun Wang (Universidade Estadual de Maringá, 2024)
The objective of this study is to explore the impact of personality traits on the attitude of Chinese population towards COVID-19 vaccine. In this study, the Chinese Big Five Personality Scale and the self-designed COVID-19 Vaccine Attitude Scale were used to investigate the population in Shanxi Province, China. Through quantitative analysis of the valid data from 492 participants, this study found that there were demographic differences among Shanxi residents in personality traits and attitude towards COVID-19 vaccine (ATCV). In the correlation analysis between the Five-factor model of personality traits and ATCV, three items of ATCV were positively correlated with conscientiousness, agreeableness, openness and extroversion, and one item of ATCV (effectiveness of COVID-19 vaccine) was weakly negatively correlated with neuroticism. In the canonical correlation analysis, conscientiousness played a major role in personality traits, and the 'effectiveness' item in ATCV played a major role. Different personality traits and demographic factors are recommended to be integrated into the category of comprehensive consideration in the process of COVID-19 vaccine promotion and health education, and the relevant theoretical results of health communication can be combined to achieve better effects.